Farmer Livelihood Strategies and Attitudes in Response to Climate Change in Agroforestry Systems in Kedougou, Senegal - Papa, C.; Nzokou, Pascal; Mbow, Cheikh (Environmental Management, 2020)
openalex: W3032744518 mag: 3032744518
Keywords: openalex:import

The Contribution of Trees Outside of Forests to Landscape Carbon and Climate Change Mitigation in West Africa - Skole, David L.; Samek, Jay H.; Dieng, Moussa; Mbow, Cheikh (Forests, 2021)
While closed canopy forests have been an important focal point for land cover change monitoring and climate change mitigation, less consideration has been given to methods for large scale measurements of trees outside of forests. Trees outside of forests are an important but often overlooked natural resource throughout sub-Saharan Africa, providing benefits for livelihoods as well as climate change mitigation and adaptation. In this study, the development of an individual tree cover map using very high-resolution remote sensing and a comparison with a new automated machine learning mapping product revealed an important contribution of trees outside of forests to landscape tree cover and carbon stocks in a region where trees outside of forests are important components of livelihood systems. Here, we test and demonstrate the use of allometric scaling from remote sensing crown area to provide estimates of landscape-scale carbon stocks. Prominent biomass and carbon maps from global-scale remote sensing greatly underestimate the “invisible” carbon in these sparse tree-based systems. The measurement of tree cover and carbon in these landscapes has important application in climate change mitigation and adaptation policies.
openalex: W3216773468 mag: 3216773468
Keywords: openalex:import

Achieving mitigation and adaptation to climate change through sustainable agroforestry practices in Africa - Mbow, Cheikh; Smith, Pete; Skole, David L.; Duguma, Lalisa; Bustamante, Mercedes M. C. (Current Opinion in Environmental Sustainability, 2014)
Agroforestry is one of the most conspicuous land use systems across landscapes and agroecological zones in Africa. With food shortages and increased threats of climate change, interest in agroforestry is gathering for its potential to address various on-farm adaptation needs, and fulfill many roles in AFOLU-related mitigation pathways. Agroforestry provides assets and income from carbon, wood energy, improved soil fertility and enhancement of local climate conditions; it provides ecosystem services and reduces human impacts on natural forests. Most of these benefits have direct benefits for local adaptation while contributing to global efforts to control atmospheric greenhouse gas concentrations. This paper presents recent findings on how agroforestry as a sustainable practice helps to achieve both mitigation and adaptation objectives while remaining relevant to the livelihoods of the poor smallholder farmers in Africa.
openalex: W2035787054 mag: 2035787054
Keywords: openalex:import

Achieving mitigation and adaptation to climate change through sustainable agroforestry practices in Africa - Mbow, Cheikh; Smith, Pete; Skole, David L.; Duguma, Lalisa; Bustamante, Mercedes M. C. (Current Opinion in Environmental Sustainability, 2014)
Agroforestry is one of the most conspicuous land use systems across landscapes and agroecological zones in Africa. With food shortages and increased threats of climate change, interest in agroforestry is gathering for its potential to address various on-farm adaptation needs, and fulfill many roles in AFOLU-related mitigation pathways. Agroforestry provides assets and income from carbon, wood energy, improved soil fertility and enhancement of local climate conditions; it provides ecosystem services and reduces human impacts on natural forests. Most of these benefits have direct benefits for local adaptation while contributing to global efforts to control atmospheric greenhouse gas concentrations. This paper presents recent findings on how agroforestry as a sustainable practice helps to achieve both mitigation and adaptation objectives while remaining relevant to the livelihoods of the poor smallholder farmers in Africa.
openalex: W2035787054 mag: 2035787054
Keywords: openalex:import

Achieving mitigation and adaptation to climate change through sustainable agroforestry practices in Africa - Mbow, Cheikh; Smith, Pete; Skole, David L.; Duguma, Lalisa; Bustamante, Mercedes M. C. (Current Opinion in Environmental Sustainability, 2014)
Agroforestry is one of the most conspicuous land use systems across landscapes and agroecological zones in Africa. With food shortages and increased threats of climate change, interest in agroforestry is gathering for its potential to address various on-farm adaptation needs, and fulfill many roles in AFOLU-related mitigation pathways. Agroforestry provides assets and income from carbon, wood energy, improved soil fertility and enhancement of local climate conditions; it provides ecosystem services and reduces human impacts on natural forests. Most of these benefits have direct benefits for local adaptation while contributing to global efforts to control atmospheric greenhouse gas concentrations. This paper presents recent findings on how agroforestry as a sustainable practice helps to achieve both mitigation and adaptation objectives while remaining relevant to the livelihoods of the poor smallholder farmers in Africa.
openalex: W2035787054 mag: 2035787054
Keywords: openalex:import; openalex:yes

Achieving mitigation and adaptation to climate change through sustainable agroforestry practices in Africa - Mbow, Cheikh; Smith, Pete; Skole, David L.; Duguma, Lalisa; Bustamante, Mercedes M. C. (Current Opinion in Environmental Sustainability, 2014)
Agroforestry is one of the most conspicuous land use systems across landscapes and agroecological zones in Africa. With food shortages and increased threats of climate change, interest in agroforestry is gathering for its potential to address various on-farm adaptation needs, and fulfill many roles in AFOLU-related mitigation pathways. Agroforestry provides assets and income from carbon, wood energy, improved soil fertility and enhancement of local climate conditions; it provides ecosystem services and reduces human impacts on natural forests. Most of these benefits have direct benefits for local adaptation while contributing to global efforts to control atmospheric greenhouse gas concentrations. This paper presents recent findings on how agroforestry as a sustainable practice helps to achieve both mitigation and adaptation objectives while remaining relevant to the livelihoods of the poor smallholder farmers in Africa.
openalex: W2035787054 mag: 2035787054
Keywords: openalex:import; openalex:yes

Achieving mitigation and adaptation to climate change through sustainable agroforestry practices in Africa - Mbow, Cheikh; Smith, Pete; Skole, David L.; Duguma, Lalisa; Bustamante, Mercedes M. C. (Current Opinion in Environmental Sustainability, 2014)
Agroforestry is one of the most conspicuous land use systems across landscapes and agroecological zones in Africa. With food shortages and increased threats of climate change, interest in agroforestry is gathering for its potential to address various on-farm adaptation needs, and fulfill many roles in AFOLU-related mitigation pathways. Agroforestry provides assets and income from carbon, wood energy, improved soil fertility and enhancement of local climate conditions; it provides ecosystem services and reduces human impacts on natural forests. Most of these benefits have direct benefits for local adaptation while contributing to global efforts to control atmospheric greenhouse gas concentrations. This paper presents recent findings on how agroforestry as a sustainable practice helps to achieve both mitigation and adaptation objectives while remaining relevant to the livelihoods of the poor smallholder farmers in Africa.
openalex: W2035787054 mag: 2035787054
Keywords: openalex:import

Importance Value Index and Species Relative Contribution to Carbon Stocks in Savanna Ecosystems : Implications for Climate Change Mitigation and Forest Management in Patako Forest (Senegal) - Sambou, Soussou; Faye, Laurice Codou; Diop, Fatimata Niang; Dieng, Serigne Ibra Mbacké; Mbow, Cheikh (Zenodo (CERN European Organization for Nuclear Research), 2022)
openalex: W4297207341
Keywords: openalex:import

Agroforestry solutions to address food security and climate change challenges in Africa - Mbow, Cheikh; Noordwijk, Meine van; Luedeling, Eike; Neufeldt, Henry; Minang, Peter A.; Kowero, G.S. (Current Opinion in Environmental Sustainability, 2014)
Trees inside and outside forests contribute to food security in Africa in the face of climate variability and change. They also provide environmental and social benefits as part of farming livelihoods. Varied ecological and socio-economic conditions have given rise to specific forms of agroforestry in different parts of Africa. Policies that institutionally segregate forest from agriculture miss opportunities for synergy at landscape scale. More explicit inclusion of agroforestry and the integration of agriculture and forestry agendas in global initiatives on climate change adaptation and mitigation can increase their effectiveness. We identify research gaps and overarching research questions for the contributions in this special issue that may help shape current opinion in environmental sustainability.
openalex: W2084863124 mag: 2084863124
Keywords: openalex:import

Agroforestry solutions to address food security and climate change challenges in Africa - Mbow, Cheikh; Noordwijk, Meine van; Luedeling, Eike; Neufeldt, Henry; Minang, Peter A.; Kowero, G.S. (Current Opinion in Environmental Sustainability, 2014)
Trees inside and outside forests contribute to food security in Africa in the face of climate variability and change. They also provide environmental and social benefits as part of farming livelihoods. Varied ecological and socio-economic conditions have given rise to specific forms of agroforestry in different parts of Africa. Policies that institutionally segregate forest from agriculture miss opportunities for synergy at landscape scale. More explicit inclusion of agroforestry and the integration of agriculture and forestry agendas in global initiatives on climate change adaptation and mitigation can increase their effectiveness. We identify research gaps and overarching research questions for the contributions in this special issue that may help shape current opinion in environmental sustainability.
openalex: W2084863124 mag: 2084863124
Keywords: openalex:import

Agroforestry solutions to address food security and climate change challenges in Africa - Mbow, Cheikh; Noordwijk, Meine van; Luedeling, Eike; Neufeldt, Henry; Minang, Peter A.; Kowero, G.S. (Current Opinion in Environmental Sustainability, 2014)
Trees inside and outside forests contribute to food security in Africa in the face of climate variability and change. They also provide environmental and social benefits as part of farming livelihoods. Varied ecological and socio-economic conditions have given rise to specific forms of agroforestry in different parts of Africa. Policies that institutionally segregate forest from agriculture miss opportunities for synergy at landscape scale. More explicit inclusion of agroforestry and the integration of agriculture and forestry agendas in global initiatives on climate change adaptation and mitigation can increase their effectiveness. We identify research gaps and overarching research questions for the contributions in this special issue that may help shape current opinion in environmental sustainability.
openalex: W2084863124 mag: 2084863124
Keywords: openalex:import

Agroforestry solutions to address food security and climate change challenges in Africa - Mbow, Cheikh; Noordwijk, Meine van; Luedeling, Eike; Neufeldt, Henry; Minang, Peter A.; Kowero, G.S. (Current Opinion in Environmental Sustainability, 2014)
Trees inside and outside forests contribute to food security in Africa in the face of climate variability and change. They also provide environmental and social benefits as part of farming livelihoods. Varied ecological and socio-economic conditions have given rise to specific forms of agroforestry in different parts of Africa. Policies that institutionally segregate forest from agriculture miss opportunities for synergy at landscape scale. More explicit inclusion of agroforestry and the integration of agriculture and forestry agendas in global initiatives on climate change adaptation and mitigation can increase their effectiveness. We identify research gaps and overarching research questions for the contributions in this special issue that may help shape current opinion in environmental sustainability.
openalex: W2084863124 mag: 2084863124
Keywords: openalex:import

Agroforestry solutions to address food security and climate change challenges in Africa - Mbow, Cheikh; Noordwijk, Meine van; Luedeling, Eike; Neufeldt, Henry; Minang, Peter A.; Kowero, G.S. (Current Opinion in Environmental Sustainability, 2014)
Trees inside and outside forests contribute to food security in Africa in the face of climate variability and change. They also provide environmental and social benefits as part of farming livelihoods. Varied ecological and socio-economic conditions have given rise to specific forms of agroforestry in different parts of Africa. Policies that institutionally segregate forest from agriculture miss opportunities for synergy at landscape scale. More explicit inclusion of agroforestry and the integration of agriculture and forestry agendas in global initiatives on climate change adaptation and mitigation can increase their effectiveness. We identify research gaps and overarching research questions for the contributions in this special issue that may help shape current opinion in environmental sustainability.
openalex: W2084863124 mag: 2084863124
Keywords: openalex:import

Mapping Vulnerability to Climate Change in Malawi: Spatial and Social Differentiation in the Shire River Basin - Coulibaly, Jeanne Y.; Mbow, Cheikh; Sileshi, Gudeta W.; Beedy, Tracy; Kundhlande, Godfrey; Musau, John (American Journal of Climate Change, 2015)
This article analyses vulnerability to climate related shocks across five districts in the shire river basin of Malawi.The analysis employs an indicator approach that integrates biophysical and socio-economic indices.Principal component statistical analysis was used to calculate an index for adaptive capacity, sensitivity and exposure to climate impact for each of the five districts.These indices were aggregated to develop a vulnerability index differentiated also by gender for the surveyed districts.The results showed that Chikwawa, Machinga and Blantyre appear to be more vulnerable to climate related shocks compared with Mwanza and Zomba.Women in Chikwawa are also found to be the most susceptible to the climate hazards impacts.To reduce vulnerability to climate impact, the study suggests that the national adaptation strategies adopted by the government should be mainstreamed into specific local adaptation actions that can be accessible and adopted by the community.Specific emphasis should be given to the improvement of women's welfare through better access to productive assets and resources.
openalex: W1744774458 mag: 1744774458
Keywords: openalex:import

Agroforestry as a solution for multiple climate change challenges in Africa - Mbow, Cheikh; Toensmeier, Eric; Brandt, Martin S.; Skole, David L.; Dieng, Moussa; Garrity, D. P.; Poulter, B. (2020)
openalex: W3024886716 mag: 3024886716
Keywords: openalex:import

Farmers’ Strategies for Adapting to and Mitigating Climate Variability and Change through Agroforestry in Ethiopia and Kenya - Bishaw, Badege; Neufeldt, Henry; Mowo, Jeremias; Abdelkadir, Abdu; Muriuki, Jonathan; Dalle, Gemedo; Tewodros, Assefa; Guillozet, Kathleen; Kassa, Habtemariam; Dawson, Ian K.; Luedeling, Eike; Mbow, Cheikh (2013)
I would like to thank the World Agroforestry Center (ICRAF), Nairobi, Kenya, for providing funds through the USAID Linkage Project to initiate collaborative research, student and faculty exchange, and the exchange of scientific information between Oregon State University and the World Agroforestry Center. Also, Oregon State University, the Wondo Genet College of Forestry and Natural Resources, Hawassa University, Hawassa, Ethiopia, the Institute of Biodiversity Conservation (IBC), Addis Ababa, Ethiopia, and the Center for International Forestry Research (CIFOR), Addis Ababa, Ethiopia.
openalex: W1535089209 mag: 1535089209
Keywords: openalex:import

Climate Factors Play a Limited Role for Past Adaptation Strategies in West Africa - Mertz, Ole; Mbow, Cheikh; Nielsen, Jonas Østergaard; Maïga, Abdou; Diallo, Drissa; Reenberg, Anette; Diouf, Awa; Barbier, Bruno; Moussa, Ibrahim Bouzou; Zorom, Malicki; Ouattara, Ibrahim; Dabi, Daniel (Ecology and society, 2010)
The Sudano-Sahelian zone of West Africa has experienced recurrent droughts since the mid-1970s and today there is considerable concern for how this region will be able to adapt to future climate change.To develop well targeted adaptation strategies, the relative importance of climate factors as drivers of land use and livelihood change need to be better understood.Based on the perceptions of 1249 households in five countries across an annual rainfall gradient of 400-900 mm, we provide an estimate of the relative weight of climate factors as drivers of changes in rural households during the past 20 years.Climate factors, mainly inadequate rainfall, are perceived by 30-50% of households to be a cause of decreasing rainfed crop production, whereas a wide range of other factors explains the remaining 50-70%.Climate factors are much less important for decreasing livestock production and pasture areas.Increases in pasture are also observed and caused by improved tenure in the driest zone.Adaptation strategies to declining crop production include 'prayer' and migration in the 400-500 mm zone; reforestation, migration, and government support in the 500-700 mm zone; and soil improvement in the 700-900 mm zone.Declining livestock holdings are countered by improved fodder resources and veterinary services.It is concluded that although rainfed crop production is mainly constrained by climate factors, livestock and pasture are less climate sensitive in all rainfall zones.This needs to be reflected in national adaptation strategies in the region.
openalex: W2289777700 mag: 2289777700
Keywords: openalex:import

Linking climate factors, agricultural development and adaptation strategies in the Sahel-Sudan zone of West Africa - Mertz, Ole; Mbow, Cheikh; Nielsen, Jonas Østergaard; Ka, Alioune; Diallo, Drissa; Cissé, Pierre; Barbier, Bruno; Da, D E; Bouzou, I; Mato, W M; Dabi, Daniel; Ihemegbulem, V (IOP Conference Series: Earth and Environmental Science, 2009)
openalex: W2136605972 mag: 2136605972
Keywords: openalex:import

Impact of climate change on the habitat range and distribution of Cordyla pinnata, Faidherbia albida and Balanites aegyptiaca in Senegal - Sambou, Mariama; Koné, Brahima; Sané, Seyni; Vodounnon, Mahunan Eric José; Diatta, André A.; Diatta, Lamine; Sambou, Bienvenu; Diop, Fatimata Niang; Sambou, Soussou; Diatta, Malaïny; Sambou, Hyacinthe; Goudiaby, Assane; et al. (Modeling Earth Systems and Environment, 2024)
openalex: W4391650208
Keywords: openalex:import

A New Multiple Imputation Approach Using Machine Learning to Enhance Climate Databases in Senegal - Touré, Mory; Klutse, Nana Ama Browne; Sarr, Mamadou Adama; Kenne, Annine Duclaire; Bhuiyanr, Md Abul Ehsan; Ndiaye, Ousmane; Badiane, Daouda; Thiaw, Wassila M.; Sy, Ibrahima; Mbow, Cheikh; Sall, Saïdou Moustapha; Gaye, Amadou Thierno (Research Square (Research Square), 2023)
Abstract This study aims at enhancing climate data in Senegal using information from the Global Surface Summary of the Day (GSOD). It uses data from 1991 to 2022 from major secondary synoptic stations in Senegal. These data are subject to missing values (data gaps). To address these gaps, multiple imputation was used based on three machine learning models: PMM (Predictive Mean Matching), RF (Random Forest), and NORM (Bayesian Linear Regression). The PMM model relies on averages of similar data, the RF model handles complex relationships between variables, even on an intra-seasonal scale, while the NORM model captures seasonal variations and extreme values. The results highlight the higher performance of the RF model in terms of accuracy and variance explanation compared to the others. The findings of this study open new avenues for informed decision-making in sectors such as agriculture and urban planning, where accurate climate data play a crucial role. However, while this study lays the groundwork for better utilization of climate data in Senegal, challenges persist, including the ongoing need to collect high-quality data and adapt models to data intricacies.
openalex: W4386253445
Keywords: openalex:import

Adaptation strategies and climate vulnerability in the Sudano‐Sahelian region of West Africa - Mertz, Ole; Mbow, Cheikh; Reenberg, Anette; Genesio, L.; Lambin, Éric F.; D’haen, Sarah; Zorom, Malicki; Rasmussen, Kjeld; Diallo, Drissa; Barbier, Bruno; Moussa, Ibrahim Bouzou; Diouf, Awa; et al. (Atmospheric Science Letters, 2011)
Abstract Rural development in the Sudano‐Sahelian region during the past 20 years and future scenarios of change were studied using meta‐analysis of case studies, household interviews and scenario assessment. Households have generally increased their wealth, especially when they diversify out of agriculture. Rain‐fed crop cultivation is more sensitive to climate factors than livestock, but generally climate factors play a limited direct role for local land use and livelihood strategies. The agricultural sector needs strong support to remain important in the region and off‐farm work and migration are likely to continue to increase, which may decrease vulnerability. Copyright © 2011 Royal Meteorological Society
openalex: W2061336752 mag: 2061336752
Keywords: openalex:import